Assessment of the Rapid Immunochromatographic Test as a Diagnostic Tool for Norovirus Related Diarrhea in Children - Ranuh, Reza Gunadi; Athiyyah, Alpha Fardah; PA, Deanty Ayu; Darma, Andy; Raharjo, Dadik; Shirakawa, Toshiro; Sudarmo, Subijanto Marto (Folia Medica Indonesiana, 2019)
In developing countries, Norovirus is the second-leading cause of acute diarrhea, after rotavirus. The approved gold standard method for diagnosis of norovirus infection is RT-PCR. The rapid immunochromatographic test is a novel and expedient method for diagnosing norovirus that is relatively affordable. However, the use of the rapid immunochromatographic test remains controversial because of its accuracy. This study aimed to explore whether the rapid immunochromatographic test could be used for diagnosing norovirus-related diarrhea in children. Rapid immunochromatographic test (QuickNaviTM-Norovirus2) and RT-PCR on stool samples was used to diagnose norovirus. Stool samples were obtained from pediatric patients aged between 1 and 60 months who had diarrhea and were admitted to the pediatric ward at Dr. Soetomo General Hospital Surabaya, between April 2013 and March 2014. Ninety-four subjects provided stool samples that were tested using QuickNaviTM-Noro2 and RT-PCR. Using the test, 64 samples tested positive for norovirus and 30 tested negatives. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the rapid immunochromatographic test were consecutively 90.3%, 42.9%, 43.8%, 90%, and 58.5%. RT-PCR was used to test all samples to assess the accuracy, which showed that one from 31 samples contained the GI strain (1.1%), while 30 samples (32%) contained the GII strain. This study definitively establishes that the rapid immunochromatography test is not sufficiently accurate for use as a screening or diagnostic tool in norovirus-related diarrhea cases in children.